2008
DOI: 10.1371/journal.pone.0002954
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clinical Evaluation of a Novel Nanoemulsion-Based Hepatitis B Mucosal Vaccine

Abstract: BackgroundHepatitis B virus infection remains an important global health concern despite the availability of safe and effective prophylactic vaccines. Limitations to these vaccines include requirement for refrigeration and three immunizations thereby restricting use in the developing world. A new nasal hepatitis B vaccine composed of recombinant hepatitis B surface antigen (HBsAg) in a novel nanoemulsion (NE) adjuvant (HBsAg-NE) could be effective with fewer administrations.Methodology and Principal FindingsPh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
135
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 67 publications
7
135
0
Order By: Relevance
“…In other studies, when an NE adjuvant prototype was combined with purified antigens such as recombinant anthrax protective antigen (8) and HIV gp120, it elicited a Th1 systemic response with neutralizing serum antibodies and mucosal IgA when it was administered intranasally to mice or guinea pigs (9). W 80 5EC NE combined with hepatitis B virus surface antigen and administered intranasally produced an enhanced immune response and caused no inflammation in the nasal cavity, no histopathological changes in key organs, and no abnormal laboratory findings in safety studies performed with mice, rats, guinea pigs, and dogs (23). These data suggest a broad adjuvant activity for the W 80 5EC NE and an acceptable safety profile for this adjuvant.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In other studies, when an NE adjuvant prototype was combined with purified antigens such as recombinant anthrax protective antigen (8) and HIV gp120, it elicited a Th1 systemic response with neutralizing serum antibodies and mucosal IgA when it was administered intranasally to mice or guinea pigs (9). W 80 5EC NE combined with hepatitis B virus surface antigen and administered intranasally produced an enhanced immune response and caused no inflammation in the nasal cavity, no histopathological changes in key organs, and no abnormal laboratory findings in safety studies performed with mice, rats, guinea pigs, and dogs (23). These data suggest a broad adjuvant activity for the W 80 5EC NE and an acceptable safety profile for this adjuvant.…”
Section: Discussionmentioning
confidence: 97%
“…W 80 5EC NE contains droplets of approximately 400 nm in diameter and has inherent antimicrobial activity (23). Studies with a prototype NE formulations showed that the NE can inactivate whole influenza virus and induce an immune response after nasal administration that protects mice from homologous influenza virus challenge (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently developed a mucosal nanoemulsion (NE) adjuvant, W 80 5EC, that does not contain known TLR or other innate receptor ligands but is able to enhance both humoral and cellular immunity (27,31,32). This NE adjuvant is simply an oil-in-water formulation of emulsified, highly refined soybean oil combined with nonionic and cationic surfactants and ethanol, and it is similar in size to many viruses that infect the nasal mucosa (32).…”
mentioning
confidence: 99%
“…The potent nanotoxoid formulations provide a viable anti-virulence approach to combat with microorganisms that contain membrane damaging toxins, such as Staphylococcus aureus and Group A streptococcal infections [34]; (2) Stable at Room Temperature The common adjuvant-Alum is known to cause irritation if it is used in the conventional hepatitis B vaccine. However, the use of needle-free nasal immunization with a combination of nanoemulsion and hepatitis B antigen was found to be tolerable, effective and safe without side effects [35]. The solvent extraction or evaporation from a W/O/W (water-in-oil-in water) emulsion is usually used to prepare the antigen-encapsulated nanoparticles [36].…”
Section: Perspectivementioning
confidence: 99%